Effects of Microalgal Blooms on Aquaculture and Fisheries - Patricio A. Díaz; Gonzalo Álvarez (Fishes, 2023)
Pigmented planktonic microalgae (phytoplankton) are primary producers that form the basis of marine trophic webs [...]